Aplikasi Rekomendasi Metode Analisis Sesuai dengan Karakter Data - Andre Gunawan; Henry Novianus Palit; Andreas Handojo (Jurnal Infra, 2018)
Data has become a very valuable asset in the company, but the more powerful than the data is information that we can though from the data. The information we get from the data has many benefits. In business decision making the data has a big role to determine whether the business action taken can lead to a good foot in the company. Companies that underlie data-driven decision making (Data-Driven Decision Making) are referred to as Data-Driven Company this in general has a division that is engaged in Business Intelligence.Business Intelligence is an integrated system that provides facts / information from data that has been processed for the benefit of decision making. This system is in charge of providing decision support for the specific purpose of a business process. The foundation of Business Intelligence is data that has been processed into useful information for the decision support process. Business Intelligence uses a multitude of methods to extract information from existing data. Business Intelligence provides information at the right time, to the right person in easy-to-understand form.